The landscape of molecular chaperones across human tissues reveals a layered architecture of core and variable chaperones - Netta Shemesh (Nature Portfolio, 2021)
Tissue-specific differences in protein folding capacities are poorly understood. Here, the authors show that the human chaperone system consists of ubiquitous core chaperones and tissue-specific variable chaperones, perturbation of which leads to tissue-specific phenotypes.